Effect of nursing teaching program on knowledge and self-management behaviors for patients with essential hypertension - Abd Alaleam, Shymaa Helmy Ahmed; Mohammad, Zeinab Abd El-Latif; El-dien, Mohammed Hossam; Zaki Azer, Sahra (International Journal of Advanced Nursing Studies, 2018)
Background: Essential hypertension is the most common cardiovascular disease (CVD), affecting about one billion individuals worldwide.Aim of the study: was to evaluate the effect of nursing teaching program on knowledge and self-management behaviors for patients with essential hypertension. Study design; quasi-experimental research design was utilized to conduct this study.Setting: The study was conducted in the internal medicine department and outpatient clinics at Assiut University Hospital.Sample: Sixty adult patients of both sexes divided equally into 2 groups study and control group (thirty for each). Tools; four tools were used for data collection; Patients, assessment sheet, Hypertension Knowledge-Level Scale (HK-LS), Hypertension Self-Management Be-havior Questionnaire (HSMBQ)â€ and Nursing Teaching Program. Results; the majority of the study and control groups were female (83.3%, 66.7%), married (80.0%, 86.7%), illiterate (66.7%, 60.0), and house wives (83.3%, 63.3%).Conclusion: Nursing teaching program was effective in improving patientsâ€™ knowledge and self-management behaviors. Recommenda-tions; educational program should be planned and offered to patients on regular basis. Simple booklets should be available for patients to provide them with simple explanation about the disease.Â